ANALISIS STRATEGI PROMOSI DALAM UPAYA MENINGKATKAN KUNJUNGAN WISATA DI TAMAN HUTAN KOTA (TAMAN BONDAS) BATU - Abdiel Remalya Suliyanto; Sunarti Sunarti; Edriana Pangestuti (Fakultas Ilmu Administrasi Universitas Brawijaya, 2018)
Batu Tourism City is one of the areas in East Java Province that focuses on tourism development, especially through green open space. The City Forest Park (Taman Bondas) Batu is one of the green open spaces in Batu Tourism City which is still deserted due to lack of promotion is existence, so the researcher raises the title